Confirmation and prevention of vapor bypass in absorption heat pump with U-pipe pressure separation device caused by upward side two-phase flow. (October 2021) - Zhu, Chaoyi; Xie, Xiaoyun; Jiang, Yi
Highlights: Indication that two-phase flow in U-pipe causes vapor bypass in absorption heat pump. Observation of vapor bypass in U-Pipe through experiment under vacuum condition. Evaluation of effects of vapor bypass in AHP through field tests. New design method to avoid vapor bypass and improve performance by over 6 %. Abstract: A U-pipe is the key pressure separation device in a lithium bromide absorption heat pump (AHP) connecting the high-pressure condenser and the low-pressure evaporator. A recent study reported that two-phase flow occurs in the upward side of the U-pipe, which reduces the overall density of the fluid and impairs the pressure separation ability of the U-pipe. The liquid seal function of the U-pipe fails, and the vapor can flow directly from the high-pressure condenser to the low-pressure evaporator, causing a vapor bypass problem. This study experimentally investigates the U-pipe vapor bypass mass flow rate under vacuum conditions. The mass flow rate ratio of the bypassed vapor to the main liquid fluid in the U-Pipe can be as high as 10 %. The effect of this bypassed vapor on the AHP performance is investigated through simulations and field tests. The cooling coefficient of performance (COP) drops by 0.05 to 0.1 when vapor bypass occurs, providing evidence for the existence of U-pipe vapor bypass in AHPs. A practical method is suggested to solve this problem and to improve the cooling COP of the AHP by more than 6%.